Understanding the role of entrepreneurial behavior in SMEs - Akala, Adesoji (2015)
From my real life experience and as a student studying in the University of Jyväskylä, I have developed an interest on the importance of becoming either a philanthropist or industrialist. This actually led to my inquiry into the world of a social and business enterprise in relationship to how they impact the society. The study of Entrepreneurship therefore has broaden my ideology on business and this has led to knowing about the conflicting views of its definition and what makes a successful entrepreneur? The following research work will examine how Entrepreneurial behavior interpretes to the growth of a business enterprise and what are the behavior(s) that encourages exploration and exploitation employed by owners/managers in a firm. In the introduction part of this work, the theoretical background is given along with a definition of the study scope and emphasis placed on earlier studies on entrepreneurial behavior and review of theories.